2002
DOI: 10.1088/0953-8984/14/8/329
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of the electron spin resonance of Co2+in Zn2(OH)PO4and Mg2(OH)AsO4

Abstract: Electron spin-resonance experiments were performed on Co 2+ substituting for Zn 2+ or Mg 2+ in powder samples of Zn 2 (OH)PO 4 and Mg 2 (OH)AsO 4 . These two compounds are iso-structural and contain the Co 2+ in two environments with approximately octahedral and trigonal bipyramidal structures. The observed resonances are described using a theoretical model that considers the departures from the two perfect structures. It is shown that resonance in the pentacoordinated complex is allowed, and the crystal field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…We found that for the system parameters obtained from the optical spectra we should expect that the ground doublet be M J = ±1/2, corresponding to an allowed spectrum. The rather small intensity, of this type of spectra seems to indicate a preference of Co 2+ for the octahedral sites in the crystal structure, a conjecture that was advanced in a preliminary report [32] on the ESR of impurities of this ion in Mg 2 (OH)AsO 4 , and was confirmed in [3]. Employing a molecular calculation we have verified in the last reference that the formation energies of the two type of complexes, with both Co and Zn as the central ions, are compatible with this hypothesis.…”
Section: The Co 2+ In a Deformed Trigonal Bipyramidmentioning
confidence: 67%
See 4 more Smart Citations
“…We found that for the system parameters obtained from the optical spectra we should expect that the ground doublet be M J = ±1/2, corresponding to an allowed spectrum. The rather small intensity, of this type of spectra seems to indicate a preference of Co 2+ for the octahedral sites in the crystal structure, a conjecture that was advanced in a preliminary report [32] on the ESR of impurities of this ion in Mg 2 (OH)AsO 4 , and was confirmed in [3]. Employing a molecular calculation we have verified in the last reference that the formation energies of the two type of complexes, with both Co and Zn as the central ions, are compatible with this hypothesis.…”
Section: The Co 2+ In a Deformed Trigonal Bipyramidmentioning
confidence: 67%
“…The average of the g factors of the intense spectra is 4.15 in the two compounds, a value close to the 4.33 expected for Co 2+ in moderately distorted octahedral symmetry [29], and it seems reasonable to assign these spectra to that environment and apply the same approach employed in the previous section in the study of the ESR of Co 2+ in NH 4 NiPO 4 .6H 2 O (see also [2]). The remaining lines are very weak and we assign them to the penta-coordinated symmetry (the possible reason for their small intensity has been discussed in [3]). …”
Section: The Co 2+ In a Deformed Trigonal Bipyramidmentioning
confidence: 77%
See 3 more Smart Citations